2007
DOI: 10.1021/jp066831u
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Structure Bias in Generalized Born Solvent Models:  Comparison of Conformational Ensembles and Free Energy of Solvent Polarization from Explicit and Implicit Solvation

Abstract: The effects of the use of three generalized Born (GB) implicit solvent models on the thermodynamics of a simple polyalanine peptide are studied via comparing several hundred ns of well-converged replica exchange molecular dynamics (REMD) simulations using explicit TIP3P solvent to REMD simulations with the GB solvent models. It is found that when compared to REMD simulations using TIP3P, the GB REMD simulations contain significant differences in secondary structure populations; most notably an over-abundance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
160
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(171 citation statements)
references
References 51 publications
9
160
2
Order By: Relevance
“…7,15,17 We chose helical deca-alanine as a test case due to its simple repeating sequence, and the fact that it has been the subject of previous studies and is known to display some level of helicity. 18 We first created helical deca-alanine ͑Ace-Ala 10 -NH 2 ͒ by setting all / dihedral angles to −57.8°/ −47.0°. The leap and antechamber modules of the MD program AMBER9 ͑Ref.…”
Section: ͑4͒mentioning
confidence: 99%
“…7,15,17 We chose helical deca-alanine as a test case due to its simple repeating sequence, and the fact that it has been the subject of previous studies and is known to display some level of helicity. 18 We first created helical deca-alanine ͑Ace-Ala 10 -NH 2 ͒ by setting all / dihedral angles to −57.8°/ −47.0°. The leap and antechamber modules of the MD program AMBER9 ͑Ref.…”
Section: ͑4͒mentioning
confidence: 99%
“…This provides a potential contrast with a recent computational study of trpzip2 that used the same force field and TIP3P explicit solvent, 16 which found a folding free energy close to −0.5 kcal/mol at 273 K. However, this divergence is unsurprising, given that previous studies comparing implicit and explicit solvent have shown that GB models tend to overstabilize α-helical conformations. [40][41][42] As indicated by the potential of mean force versus D rms at 293 K in Fig. 2, this effect need not be large to destabilize the native state in the context of ff99SB.…”
Section: Discussionmentioning
confidence: 90%
“…Despite its documented successes, there is a clear sense in the modeling community that the canonical GB approximation is still a much less faithful representation of reality than the standard numerical PE (PB) implicit solvation treatment, 50 let alone the more fundamental explicit solvation framework. 27,[50][51][52] For example, it appears that the GB does not have the right balance between intrasolute and solvent-solute charge-charge interactions, resulting in overstabilization of salt bridges; [52][53][54] erroneous salt bridges appear to be a generic property of various GB flavors.…”
Section: B Known Accuracy Limitations Of the Canonical Gbmentioning
confidence: 99%
“…27,[50][51][52] For example, it appears that the GB does not have the right balance between intrasolute and solvent-solute charge-charge interactions, resulting in overstabilization of salt bridges; [52][53][54] erroneous salt bridges appear to be a generic property of various GB flavors. 51 And while some of the discrepancies (relative to the explicit solvent results) are already present at the continuum solvent (PE) level, the rest come directly from the approximations of the PE → GB step.…”
Section: B Known Accuracy Limitations Of the Canonical Gbmentioning
confidence: 99%